COVID-19 vaccine hesitancy in patients with systemic autoimmune rheumatic disease: an interview-based survey - Gaur, Priyanka; Agrawat, Hardik; Shukla, Anuj (Rheumatology international, 2021)
Patients with a systemic autoimmune rheumatic disease (AIRD) are vulnerable to SARS Cov-2 infection. Vaccination against this infection can prevent the patients from developing severe disease. But vaccine hesitancy in this group can emerge as a hurdle. So there is a need to understand the perception regarding vaccination in AIRD patients. The study is an interview-based survey done in AIRD patients and a control group from the general population. The questionnaire included the subject’s demographic details, duration, diagnosis, the activity of AIRD, and questions regarding the perception of the vaccination. The survey included 280 patients with AIRD and 102 control subjects. 54% (152/280) of the patients and 67% (68/102) of the controls were willing to get vaccinated ( p = 0.03). Patients > 45-years of age were more willing to vaccinate than those with age ≤ 45-years (61.9% vs. 44.8%; p = 0.001). Patients with lower education had more vaccine hesitancy than those with graduation and above (38% vs. 69%; p < 0.001). The common reason for vaccine hesitancy was not-yet-decided, fear related to vaccine side-effects, and disease worsening. 29% (82/280) patients were already vaccinated, out of which 35% (35/82) had mild events (fever/myalgia/headache). AIRD patients had fewer side effects than controls, and disease flare was seen in only one patient. Thus, educating AIRD patients regarding the pros and cons of vaccination, particularly concerning immunological disease, can help us overcome vaccine hesitancy. The message should clearly penetrate that there is a negligible risk of AIRD-flares with the COVID-19 immunization and the side effects are mild and manageable.